Assessment of economic feasibility of pen aquaculture technology in floodplain wetlands (beels) of Assam, India - Das, Alakesh; Bhattacharjya, B. K.; Goswami, S. N.; Sawant, P. B.; Debnath, D.; Yengkokpam, S.; Das, A.; Kakati, A.; Sarma, K. K.; Chadha, N. K.; Verma, A. K.; Sharma, A. P. (Indian Journal of Fisheries, 2018)
Floodplain wetlands (beels) constitute one of the most important fishery resources amenable for culture-based fisheries development in Assam, both in terms of large resource size (100,815 ha) and high fish production potential (1000-1500 kg ha-1 yr-1). Pen aquaculture technology standardised by ICAR-Central Inland Fisheries Research Institute (ICAR-CIFRI), Barrackpore, India for in situ rearing of carp seed for stocking in beels was demonstrated in 21 beels located in 9 districts of Assam in collaboration with the Assam Fisheries Development Corporation Limited (AFDC Ltd.) and Bodoland Territorial Council (BTC) for pilot-scale validation of economic feasibility of the technology. Large pen enclosures (2400-4990 m2) were erected in the beels for the validation; which were grouped into four size groups viz., P1 (2400-2499 m2), P2 (2500-3499 m2), P3 (3500-4499 m2) and P4 (4500-4999 m2 area) to determine the most economic size of pens for the beels of Assam. Cost of bamboo (main construction material) ranged from 30.47 (P4) to 48.74% (P3) of the capital cost. Labour cost for pen construction was found to be the major contributor of capital cost ranging from 33.73 (P3) to 52.22% (P4), followed by the cost of LDPE netting (10.56-13.74%) and coir rope (3.28-5.83%). Major share of recurring cost was spent on fish seed (54.93-61.04%), followed by feed (17.01-22.63%) and towards labour for culture operations (8.48-14.51%). The total cost per crop was the highest in P3 (`87,211/-) followed by that in P4 (`52,606/-) and P2 (`50,933/-), whereas it was the lowest in P1 (`49,511/-). The percentage expenditure of recurring costs per crop to total cost was 72.48-82.25% and a much smaller percentage (17.74-27.51%) of total cost was contributed by the cost on fixed expenditure. The average quantity of fish seed produced in the pens in P1, P2, P3 and P4 groups was 885.94, 875.08, 1,356.73 and 1,104.62 kg, respectively. The P1 group was found to be the most economically viable range of pen size yielding the highest benefit-cost ratio (3.04), followed by pen sizes P4 (2.78), P2 (2.50) and P3 (2.28). The study showed that pen aquaculture technology using pen sizes in the range of 2400-5000 m2 were economically viable for in situ carp seed rearing in the beels of Assam, with highest profitability in the pen size range of 2400-2499 m2.